Spatial Analysis of Microplastics Using the FT-IR (Fourier Transform Infrared) Method in Green Mussel Farmers' Feces - Baharuddin, Alfina; Asran, Asran; Ikhtiar, Muhammad; Suhermi (Window of Health : Jurnal Kesehatan, 2023)
Mismanagement and waste recycling are still being carried out by many countries, especially Asian countries. Indonesia's plastic waste management is the second highest globally, amounting to 3.22 million metric plastic waste/year. The same data source also estimates that every year Indonesia dumps as much as 0.48 - 1.29 million metric plastic waste into the sea, which is also the second highest in the world. This type of research is an observational research design with a descriptive approach. The sample in this study was ten people. The location of this research is the coast of Barombong, Makassar City. Data were obtained by identifying MPs in feces in the laboratory and identifying the type of polymer using FTIR (Fourier Transform Infrared). The results of the study showed that all positive samples contained microplastics. The types of MPs found were line and fragment forms, with different size and color variations. The types of polymers found in this study are Polypropylene(PP), Ethylene/Propylene Copolymer, Polyethylene(PE), Ethylene/Propylene Copolymer, High-Density Polyethylene(HDPE), Polyester Film, Polypropylene, Isotactic DuraSamplIR-II, High-Density Polyethylene(HDPE) ), Polyester Film(TOYOBO), and Tencel(LENZING Corporation). The conclusion is that the abundance of microplastics found in feces is 0.61 items/gram in the form of Fragments and Line/Fiber. The identified colors are red, transparent, blue, and black. The sizes of the microplastics found were >1 mm and 1.00-4.75 m. From the results of this study, it is recommended to reduce the use of microplastics for various activities and replace them with non-plastic or organic materials